Optimism for Naturalized Social Metaphysics: A Reply to Hawley. Issue 2 (March 2020) - Saunders, Daniel
Metaphysics has undergone two major innovations in recent decades. First, naturalistic metaphysicians have argued that our best science provides an important source of evidence for metaphysical theories. Second, social metaphysicians have begun to explore the nature of social entities such as groups, institutions, and social categories. Surprisingly, these projects have largely kept their distance from one another. Katherine Hawley has recently argued that, unlike the natural sciences, the social sciences are not sufficiently successful to provide evidence about the metaphysical nature of social entities. By contrast, I defend an optimistic view of naturalistic social metaphysics. Drawing on a case study of research into contextual effects in social epidemiology, I show that social science can provide a valuable evidence for social metaphysicians.